Perancangan Perangkat Lunak Kriptografi Citra Digital dengan FFT Kunci Chaos - Linna Oktaviana Sari (UIN Sultan Syarif Kasim Riau, 2012)
Cryptography can be performed on the image. The image is a type of digital media is most vulnerable to illegal actions. To secure the transmitted digital image, digital image must be encrypted into an image that has no meaning. However, not all encryption methods used in the text can be applied to image encryption because a slow process. This can be solved by applying a special encryption method for digital images. In this study, cryptographic software has been designed to secure the digital image using FFT as the encryption algorithm, inverse FFT as the decryption algorithm and the logistic equation of chaos as the key. The software designed to use GUI Matlab R2010a. The results showed that the cryptographic software has been designed, can make the process of encryption and decryption on digital images using algorithms FFT, IFFT and chaos as the key, with less than 1 second.Keywords: Cryptography, digital Image, FFT, Chaos.